The Assimilation of Software Process Innovations: An Organizational Learning Perspective - Fichman, Robert G.; Kemerer, Chris F. (Management Science, 1997)
The burden of organizational learning surrounding software process innovations (SPIs)—and complex organizational technologies in general—creates a “knowledge barrier” that inhibits diffusion. Attewell (Attewell, P. 1992. Technology diffusion and organizational learning the case of business computing. Organ. Sci. 3(1) 1–19.) has suggested that many organizations will defer adoption until knowledge barriers have been sufficiently lowered; however, this leaves open the question of which organizations should be more likely to innovate, even in face of high knowledge barriers. It is proposed here that organizations will innovate in the presence of knowledge barriers when the burden of organizational learning is effectively lower, either because much of the required know-how already exists within the organization, or because such knowledge can be acquired more easily or more economically. Specifically, it is hypothesized that organizations will have a greater propensity to initiate and sustain the assimilation of SPIs when they have a greater scale of activities over which learning costs can be spread (learning-related scale), more extensive existing knowledge related to the focal innovation (related knowledge), and a greater diversity of technical knowledge and activities (diversity). An empirical study using data on the assimilation of object-oriented programming languages (OOPLs) by 608 information technology organizations strongly confirmed the importance of the three hypothesized factors in explaining the assimilation of OOPLs.